2014
DOI: 10.3109/07420528.2014.933842
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal incidence of hospital admissions for Stanford type A aortic dissection

Abstract: The objective of this study was to test the hypothesis that there is seasonal variation in the incidence of Stanford type A aortic dissection (SA-AoD) among patients admitted to our cardiovascular surgical service. A sinusoidal logistic regression model was used to analyze event data for 6081 calendar days. A cyclic peak risk for SA-AoD was observed for calendar day 304 (p=0.019). The odds ratios for the 3- and 6-month window surrounding this peak were 1.6 (p=0.054) and 1.7 (p=0.0040), respectively. Our result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…This was a natural history (non-experimental) analysis of an archival de-identified dataset, in consent with the Declaration of Helsinki. Details of the study database and methodology have been previously described and are briefly summarized below [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was a natural history (non-experimental) analysis of an archival de-identified dataset, in consent with the Declaration of Helsinki. Details of the study database and methodology have been previously described and are briefly summarized below [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Of 232 potentially relevant publications initially screened, 10 eligible studies 110 were identified (Table 1). The mean of atmospheric temperature/pressure 14,68,10 and relative humidity 14,6,10 on the days with AAA and controls was available in eight studies, and the OR for AAD per unit increment of atmospheric temperature/pressure 5,7,9,10 and relative humidity 10 was reported in four studies. The OR per 1 mmHg and 1 hPa increment of pressure was converted into that per 1 kPa increment using the standard formula.…”
mentioning
confidence: 99%